2019
DOI: 10.2147/cmar.s199462
|View full text |Cite
|
Sign up to set email alerts
|

<p>Familial association of lung cancer with liver cancer in first-degree relatives</p>

Abstract: Purpose: Besides the smoking and occupational exposures, heritable factors have been proven to be a risk factor for lung cancer by several population-based studies, which would misestimate the risk of lung cancer. Patients and methods: To quantify the magnitude of the high risk of lung cancer with family history, we performed a case-based study with 1373 enrolled individuals, which may be more accurate than a population-based study. Results: Risk of lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…6 It has been reported that ALK rearrangement typically occurred in younger patients, which was also verified by our results. Family history of cancer is a predisposing factor for cancers, [16][17][18][19][20] including lung cancer. 21,22 According to our results, there was no difference in family cancer history among different age groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 It has been reported that ALK rearrangement typically occurred in younger patients, which was also verified by our results. Family history of cancer is a predisposing factor for cancers, [16][17][18][19][20] including lung cancer. 21,22 According to our results, there was no difference in family cancer history among different age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Family history of cancer is a predisposing factor for cancers, 16 – 20 including lung cancer. 21 , 22 According to our results, there was no difference in family cancer history among different age groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation